Characteristics of Limestone Formation Tonasa in Baring Area Segeri District Pangkep Regency South Sulawesi Province - Adam, Muhammad; Hasanuddin; Yunita Samalembang (Journal of Geology and Exploration, 2025)
Administratively, the Baring area is included in the area of Segeri District, Pangkep Regency, South Sulawesi Province. This study aims to determine the characteristics of the Tonasa Formation limestone. The research method is the method of observation and collection of field data and the petrographic method.The Baring area geomorphological unit is a geomorphological unit of low karst hills characterized by the presence of karst cliffs, staclactites and karst caves. Periodic and episodic river types, subsequential river genetic types, river stadia are young towards adulthood and adult area stadia towards adulthood. Characteristics of the appearance of limestone of the Tonasa Formation macroscopically in a fresh state of brownish-yellow and in a weathered state of blackish-gray, clastic texture, size of fine sand material to medium sand, unlayered structure, good sortation, closed packaging, good porosity, good permeability. And microscopically, it shows a massive structure and texture of low porosity, grain supported, 0.02 – 0.75 mm, the constituent fragments in this rock are in the form of skeletal grains/clast/fossils, minerals in the form of calcite are found with a size of 0.02 mm – 0.15 mm, mud is found replacing and filling body parts of fossils that have undergone dissolution with a size of <0.02 mm.